Cardiovascular status after Kawasaki disease in the UK. Issue 20 (27th August 2015) - Shah, V; Christov, G; Mukasa, T; Brogan, K S; Wade, A; Eleftheriou, D; Levin, M; Tulloh, RM; Almeida, B; Dillon, MJ; Marek, J; Klein, N; et al.
Abstract : Objective: Kawasaki disease (KD) is an acute vasculitis that causes coronary artery aneurysms (CAA) in young children. Previous studies have emphasised poor long-term outcomes for those with severe CAA. Little is known about the fate of those without CAA or patients with regressed CAA. We aimed to study long-term cardiovascular status after KD by examining the relationship between coronary artery (CA) status, endothelial injury, systemic inflammatory markers, cardiovascular risk factors (CRF), pulse-wave velocity (PWV) and carotid intima media thickness (cIMT) after KD. Methods: Circulating endothelial cells (CECs), endothelial microparticles (EMPs), soluble cell-adhesion molecules cytokines, CRF, PWV and cIMT were compared between patients with KD and healthy controls (HC). CA status of the patients with KD was classified as CAA present (CAA+) or absent (CAA−) according to their worst-ever CA status. Data are median (range). Results: Ninety-two KD subjects were studied, aged 11.9 years (4.3–32.2), 8.3 years (1.0–30.7) from KD diagnosis. 54 (59%) were CAA−, and 38 (41%) were CAA+. There were 51 demographically similar HC. Patients with KD had higher CECs than HC (p=0.00003), most evident in the CAA+ group (p=0.00009), but also higher in the CAA− group than HC (p=0.0010). Patients with persistent CAA had the highest CECs, but even those with regressed CAA had higher CECs than HC (p=0.011). CD105 EMPs were also higher in the KD group versus HC (p=0.04), particularly in the CAA+ group (p=0.02), with similar findings for soluble vascular cell adhesion molecule 1 and soluble intercellular adhesion molecule 1. There was no difference in PWV, cIMT, CRF or in markers of systemic inflammation in the patients with KD (CAA+ or CAA−) compared with HC. Conclusions: Markers of endothelial injury persist for years after KD, including in a subset of patients without CAA.